Expression of E6, p53 and p21 proteins and physical state of HPV16 in cervical cytologies with and without low grade lesions - Tagle, Diana K Jiménez (e-Century Publishing Corporation, 2014)
The aim of this study was to determine the correlation between expression of HPV16 E6, p53 and p21 proteins and the physical state of HPV16 in cervical cytologies without squamous intraepithelial lesions (Non-SIL) and with low grade squamous intraepithelial lesions (LSIL), both with HPV16 infection. 101 liquid-based cytological samples were analyzed. 50 samples were without squamous intraepithelial lesions (Non-IL) and 51 samples of low grade squamous intraepithelial lesions (LSIL), both with HPV16 infection. HPV16 infection was determined by PCR-RFLP, and the physical state of HPV16 by in situ hybridization with tyramide-amplification. The expression of E6, p53 and p21 proteins was evaluated by immunocytochemistry. The expression of HPV16 E6 protein was significantly higher in LSIL that in Non-SIL samples (p=0.006). We found a significant correlation between E6 expression and the physical state of HPV16 in Non-SIL (p=0.049). Our results suggest that high expression of E6 in LSIL is an early event of cervical carcinogenesis and perhaps can be used as an early marker.